2023
DOI: 10.3390/molecules28176313
|View full text |Cite
|
Sign up to set email alerts
|

Modified Rice Bran Arabinoxylan by Lentinus edodes Mycelial Enzyme as an Immunoceutical for Health and Aging—A Comprehensive Literature Review

Soo Liang Ooi,
Peter S. Micalos,
Sok Cheon Pak

Abstract: Rice bran arabinoxylan compound (RBAC) is derived from defatted rice bran enzymatically treated with Lentinus edodes mycelium. This review explores biologically active compounds and mechanisms of action that support RBAC as an immunomodulating nutraceutical in generally healthy and/or aging individuals. Thirty-seven (n = 37) primary research articles fulfilled the selection criteria for review. Most research is based on Biobran MGN-3, which consists of complex heteropolysaccharides with arabinoxylan as its pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 127 publications
0
14
0
Order By: Relevance
“…( 2019 ), and the lead author in another related publication (Ooi et al. 2023c ). Additionally, arabinoxylan from rice bran extracted through other methods, such as acid hydrolysis and bioconversion, also exhibited potent immunomodulatory effects on the non-specific immune responses, including NK cell activity (Ji et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2019 ), and the lead author in another related publication (Ooi et al. 2023c ). Additionally, arabinoxylan from rice bran extracted through other methods, such as acid hydrolysis and bioconversion, also exhibited potent immunomodulatory effects on the non-specific immune responses, including NK cell activity (Ji et al.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of the immunomodulatory effects of RBAC on other immune cells, such as monocytes and macrophages, neutrophils, and T and B lymphocytes, in healthy participants, cells, and animals can be found in a separate publication of the lead author (Ooi et al. 2023c ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have investigated the extraction of AX from by-products of conventional raw materials, revealing that AX derived from wheat bran exhibits relatively low protein content and poor emulsification (Fan et al, 2023). Additionally, AX extracted from rice bran has shown promise as a dietary supplement for regulating intestinal flora in healthy adults (Ooi et al, 2023). Furthermore, efforts have been made to extract AX from sugarcane straw to enhance the economic value of by-products (Costa Joana et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact chemical composition of the immunologically active ingredient of RBAC remains unclear, research based on MGN-3 found RBAC to be a complex polysaccharide with arabinoxylan as its primary structure (36%) while also containing galactan and glucan [ 2 ]. In preclinical experiments with healthy cells and animals, RBAC was shown to promote innate immune defences by upregulating macrophage phagocytosis and enhancing natural killer cell activity while lowering oxidative stress through strong antioxidant capacity [ 2 ]. RBAC has also been reported to augment adaptive immunity by promoting T and B lymphocyte proliferation through the induction of dendritic cell maturation.…”
Section: Introductionmentioning
confidence: 99%
“…RBAC has also been reported to augment adaptive immunity by promoting T and B lymphocyte proliferation through the induction of dendritic cell maturation. Moreover, in other preclinical studies, RBAC inhibited mast cell degranulation during allergic reactions to lower inflammation and downregulated angiogenesis by modulating cytokines and growth factors [ 2 ].…”
Section: Introductionmentioning
confidence: 99%